STATISTICAL STUDY OF ABORTION AT MEDICAL CENTRES OF ISFAHAN UNIVERSITY - MR. Akbar; B. Aflaki; TS. Azoodani; K. Ghaffari; MR. Salimi (Tehran University of Medical Sciences, 1978)
In this paper we carried out an exact statistics on the basis of total admission due to abortions, with following results: 1- Abortion incidence is 14 of total admissions. 2- 46.8 of abortions were between the 8th and 12th weeks of gestation. 3- 42,038 of the patients with abortion were 24 years old or younger (younger than 25 years of age). 4- The abortion incidence is equal in different blood groups and Rh without toward any special blood group or Rh.